2018
DOI: 10.1007/s12264-018-0304-9
|View full text |Cite
|
Sign up to set email alerts
|

Decreased β-Cell Function is Associated with Cardiovascular Autonomic Neuropathy in Chinese Patients Newly Diagnosed with Type 2 Diabetes

Abstract: The influence of β-cell function on cardiovascular autonomic neuropathy (CAN), an important diabetes-related complication, is still unclear. In this study, we aimed to investigate the association between residual β-cell function and CAN in patients newly diagnosed with type 2 diabetes. We enrolled 90 newly-diagnosed type 2 diabetic patients and 37 participants with normal glucose tolerance as controls. The patients were divided into a CAN+ group (diabetic patients with CAN, n = 20) and a CAN− group (diabetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Furthermore, associations between C-peptide and CAN in individuals with type 2 DM and renal impairment have not been addressed to date. In the present study, we observed that CAN was associated with lower C-peptide level in individuals without impaired renal function, in line with the previous findings by Yang et al [8]. In addition, in individuals with impaired renal function, Cpeptide level in the bloodstream might be out of proportion to re-duced beta cell function, because approximately half of the C-peptide level is removed by the kidney [3,9,10].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, associations between C-peptide and CAN in individuals with type 2 DM and renal impairment have not been addressed to date. In the present study, we observed that CAN was associated with lower C-peptide level in individuals without impaired renal function, in line with the previous findings by Yang et al [8]. In addition, in individuals with impaired renal function, Cpeptide level in the bloodstream might be out of proportion to re-duced beta cell function, because approximately half of the C-peptide level is removed by the kidney [3,9,10].…”
Section: Discussionsupporting
confidence: 92%
“…In individuals with type 1 DM who lack C-peptide, C-peptide replacement has been reported to increase HR variability during deep breathing, suggesting positive effects of C-peptide on autonomic nerve function [19,20]. However, relationships between C-peptide and CAN in type 2 DM has not been fully explored, although Yang et al [8] recently reported that C-peptide levels were negatively associated with CAN in 90 newly diagnosed Chinese patients with type 2 DM. Furthermore, associations between C-peptide and CAN in individuals with type 2 DM and renal impairment have not been addressed to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the latest epidemiological survey from China, the prevalence of diabetes is 10.9% in China, 26 and following lots of refractory complications, which has become a public health problem that threatens human health. [27][28][29] Diabetic neuropathic pain refers to symptoms and/or signs associated with peripheral neurological dysfunction in diabetic patients, except for other reasons, manifested mainly as symmetric multiple sensory neuropathy, characterized by burning or needleor knife-like abnormal pain in feet, lower legs, and upper limbs. These complications seriously affect patients' quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Weng and colleagues demonstrate that decreased b-cell function is associated with CAN in newly-diagnosed type 2 diabetic patients. Importantly, they found that parasympathetic nerves are more commonly and severely impaired than sympathetic nerves at the early stage of type 2 diabetes [14]. Cerebral stroke not only affects sensory and motor function, but also often causes autonomic disturbances in patients due to damage of the central autonomic network.…”
mentioning
confidence: 99%